Factors Influencing Occupational Stress: A Study on its Effect on the Performance of MSU-IIT Faculty during COVID-19 Pandemic - BANSE, JESSA MAE (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
As a response against the Coronavirus disease (COVID-19), several countries adopted online and modular programs in the educational sector. As these require certain competencies and skills, these changes might have contributed to the stress experienced by the faculty members that could affect their performance. The purpose of this study is to determine the level of occupational stress, measured by the Teacher’s Stress Inventory (TSI), that the faculty members of Mindanao State University-Iligan Institute of Technology (MSU-IIT) experienced caused by work-family conflict, lack of training, role ambiguity and role conflict, powerlessness, and intrinsic impoverishment. In addition, the impact of occupational stress on the performance of the faculty members during the school year 2020-2021 is assessed. Anchored on Michigan Model and Performance and Demand Theory of Welford, 114 faculty members were selected as respondents using quota sampling, results showed that faculty members experienced slight stress. These are manifested through minimal or low stress as measured by the manifestations of stress namely emotional, biobehavioral, and physiological-fatigue. On the factors influencing occupational stress, only work-family conflict and lack of training influence occupational stress. Since faculty members cannot enter the campus and work on a work-from-home arrangement, the distinction between office hours and free/family time is almost nonexistent. The shift in the learning modality required a new set of competencies (i.e. technology-based skills) but the sudden shift only allowed a short period of time of training. The results on the factors influencing occupational stress are consistent with the Michigan Model but inconsistent with Welford's Performance and Demand Theory; even if the demand during the pandemic has changed, the faculty experienced slight stress and performed excellently in their work.